Optimization of Flavonoid Extraction from Guava Leaves for Application in Reducing Urea Transformation in Soil - Roslan, H. (IOP Publishing Ltd, 2020)
Flavonoid group is a versatile compound as it can be used in the food, pharmaceutical, and urea fertilizer industry. Five main factors have been consistently studied for optimization, which are solid-to-solvent ratios, solvent-to-solvent ratios, the temperature of extraction medium, exposure time, and equipment power intensity. Factors Solid-to-Solvent Ratio and Time showed the greatest effects on the extraction. Response surface methodology is used to determine the best conditions for flavonoid extraction from guava leaves using an ultrasonic bath. There exist incongruencies between researchers in determining which solvent is best used for flavonoid extraction. Experimentally, the highest total flavonoid content (TFC) tested using Fe (II) colorimetry was 50.44 mg of Quercetin-equivalent per gram of dry weight leaves (mg QE/g d.w.) using 1:1:1 ratio of Water-Ethanol-Methanol (WEM), a first tri-solvent based extraction for flavonoid. Further testing via urea colorimetry shows that diluted compound of 8 of flavonoid extract can reduce urea transformation starting Day 3 of soil sampling but its performance is not at par with the commercial n-Butylphosphorothioic Triadmide (NBPT) compared in this study. Nevertheless, the effect shows a positive outlook on the extract's potential as a urease inhibitor. Â© Published under licence by IOP Publishing Ltd.